Mechanical methods of reducing blood transfusion in cardiac surgery: randomised controlled trial. Issue 7349 (1st June 2002) - McGill, Neil; O'Shaughnessy, Denise; Pickering, Ruth; Herbertson, Mike; Gill, Ravi
Abstract: Objective: To assess the effectiveness of two mechanical methods of blood conservation in reducing the need for allogeneic red blood cells or coagulation products during cardiac surgery. Design: Randomised controlled trial. Setting: Regional cardiac centre in a teaching hospital in Southampton. Participants: 263 adults aged 18-80 years undergoing elective coronary artery bypass surgery entered the study, of whom 252 completed the trial. All patients received routine perioperative care. Patients were allocated to one of three treatment groups: intraoperative cell salvage, intraoperative cell salvage with acute perioperative normovolaemic haemodilution, or no mechanical blood conservation. There were 84 patients in each group. Main outcome measures: Numbers of patients who received allogeneic blood or coagulation products, and the mean number of units of blood transfused per patient. Results: Of the patients in the intraoperative cell salvage group, 26 were given a transfusion of allogeneic blood, compared with 43 in the control group (odds ratio 0.43 (95% confidence interval 0.23 to 0.80)). The mean number of units of allogeneic blood transfused per patient in the intraoperative cell salvage group was 0.68 units (SD=1.55), compared with 1.07 (1.56) units in the control group. 32 of the patients in the intraoperative cell salvage group were given any blood product, compared with 47 in the control group (odds ratio 0.47 (0.25 to 0.89); P=0.019). Combining acute perioperative normovolaemic haemodilution with intraoperative cell salvage conferred no additional benefits. Conclusions: An intraoperative cell salvage device should be used in elective coronary artery bypass grafting. Pharmacological strategies may achieve further reductions in blood transfusions. Yet further reductions in blood transfusions could be achieved if the lower safe limit of haemoglobin concentration in patients undergoing cardiac surgery were known.